The COLAK Model for Vocabulary Learning in Primary English Classrooms - Rani Zahra; Yesi Darmayanti; Vivi Amanda; Arisman Arisman; Yondri Mei Muzaqi (Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary development is fundamental to Teaching English to Young Learners (TEYL), yet many primary English classrooms continue to rely on teacher-centred instruction with limited use of culturally relevant learning approaches. Although traditional games have been widely used as learning media, previous studies have largely treated them as supplementary classroom activities rather than structured instructional models with systematic learning procedures and multidimensional vocabulary assessment. Addressing this research gap, this study investigated how the COlourful CongkLAK (COLAK) model supports vocabulary development and student engagement in primary English classrooms. A descriptive qualitative approach supported by quantitative frequency analysis was employed with 18 second-grade students at SD Negeri 001 Rambah, Indonesia. Data were collected through structured classroom observations, observation checklists, and video recordings. The findings showed that the COLAK model effectively enhanced students' vocabulary development, particularly in word recognition, followed by pronunciation accuracy and meaning recall, while contextual word use remained the most challenging aspect. The model also promoted high levels of student engagement through meaningful interaction and collaborative learning. These findings suggest that the COLAK model provides an effective culturally responsive approach to vocabulary learning in TEYL.